Comparative analysis of CRISPR/Cas9 delivery approaches for polyphenol oxidase 2 gene editing in potato - Gonzalez, Matías Nicolás; Massa, Gabriela Alejandra; Anderson, Mariette; Decima Oneto, Cecilia Andrea; Turesson, Helle; Storani, Leonardo; Olsson, Niklas; Fält, Ann Sofie; Hofvander, Per; Feingold, Sergio Enrique (Keystone Symposia on Molecular and Cellular Biology, 2021)
Poster